2011
DOI: 10.1038/oby.2010.116
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Dysfunction in Obstructive Sleep Apnea and Type 2 Diabetes Mellitus

Abstract: Despite the high prevalence of obstructive sleep apnea (OSA) in type 2 diabetes mellitus (DM), the attributable vascular risk from each condition is unknown. We hypothesize that OSA may have a similar effect on vascular function as type 2 diabetes does. Healthy normal-weight subjects, healthy obese subjects, subjects with type 2 diabetes, and obese subjects with OSA were enrolled. Vascular function was assessed with brachial artery ultrasound for flow-mediated dilatation (FMD) and in skin microcirculation by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 25 publications
2
23
3
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19] However, despite well-recognized endothelial abnormalities of large peripheral arteries in OSA patients, scarce data are available on the complex nature of vascular/endothelial function in otherwise healthy patients with moderate-tosevere OSA. In this study, we show for the first time that, in OSA, ED assessed at the macrocirculatory and microcirculatory beds parallels with the impairment of cardiac endothelial function/perfusion.…”
Section: Butt Et Al Vascular Function In Sleep Apnea 421mentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14][15][16][17][18][19] However, despite well-recognized endothelial abnormalities of large peripheral arteries in OSA patients, scarce data are available on the complex nature of vascular/endothelial function in otherwise healthy patients with moderate-tosevere OSA. In this study, we show for the first time that, in OSA, ED assessed at the macrocirculatory and microcirculatory beds parallels with the impairment of cardiac endothelial function/perfusion.…”
Section: Butt Et Al Vascular Function In Sleep Apnea 421mentioning
confidence: 99%
“…18 In this technique, the current was delivered through 2 drug delivery chambers (model LI 611, Perimed, Jarfalla, Sweden), which were placed on the ventral aspect of the right upper forearm 5 cm apart and were connected to a current intensity-regulated generator (Perilont, Perimed AB). Mean baseline perfusion, mean maximum perfusion, and maximum percentage of change in perfusion were calculated using modern Perimed software.…”
Section: Laser Doppler Flowmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…The level of circulating MPs in peripheral blood has been reported to be increased in several ischemic diseases [7]. It seems that MPs from activated leukocytes (CD62L_ MPs) are higher in patients with OSA and a positive correlation between circulating levels of CD62L_ MPs and nocturnal hypoxemia severity has been reported [16,17,18]. Nevertheless, other authors studying children with sleep breathing disorders observed that leukocyte CD11b+ MPs and platelet CD41a+ MPs were the microparticles that correlated the best with the apnoea-hypopnea index [19].…”
Section: Discussionmentioning
confidence: 99%
“…OSAS is associated with significant systemic consequences, including cardiovascular morbidity and mortality, and the risk increases with the severity of the syndrome [3]. The pathophysiology underlying the link between OSAS and the cardiovascular system is attributed largely to systemic inflammation and oxidative stress, which are both contributors to endothelial dysfunction [4]. The treatment modalities of OSAS include Continuous Positive Airway Pressure (CPAP), weight loss, upper airway surgery, and oral devices [5].…”
Section: Editorialmentioning
confidence: 99%